2020
DOI: 10.30682/nm2001a
|View full text |Cite
|
Sign up to set email alerts
|

Tunisian consumers perception and behavior towards organic food products

Abstract: Organic agriculture production in Tunisia is relatively recent and was mainly oriented to the export market. However, local market demand is growing for such products. The objective of the current study is to assess consumers’ awareness and consumption of organic food products. A survey was implemented and included 250 respondents from the capital city Tunis. We used descriptive statistics, factor and cluster analysis to analyze the data. The results indicated that respondents’ perceptions towards organic food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The reason behind this consideration can be recognized in the need, expressed by consumer interest in sustainability issues, to receive additional information about the social, environmental and economic aspects related to the purchase of the product or the support of the brand. In fact, by revealing certain needs-such as the comprehension of the purchase impact or the uptake of the sustainable actions linked to the production, consumption and disposal of the product-and in the absence of desired indications, buyers may find themself in a position of indecision, ultimately opting to occasionally choose different products [27,54,60,67,68]. Furthermore, Model 2 also provides statistical support for Hypothesis 2.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The reason behind this consideration can be recognized in the need, expressed by consumer interest in sustainability issues, to receive additional information about the social, environmental and economic aspects related to the purchase of the product or the support of the brand. In fact, by revealing certain needs-such as the comprehension of the purchase impact or the uptake of the sustainable actions linked to the production, consumption and disposal of the product-and in the absence of desired indications, buyers may find themself in a position of indecision, ultimately opting to occasionally choose different products [27,54,60,67,68]. Furthermore, Model 2 also provides statistical support for Hypothesis 2.…”
Section: Resultsmentioning
confidence: 88%
“…In reality, this could be understood considering that consumers interested in sustainable issues may need an adequate level of information to distinguish the characteristics of different products in relation with their environmental and social impact. When this information is lacking or not consistent with the consumers' needs, as in the case of firms not leveraging sustainable marketing practices, uncertainty may affect consumers that, in turn, may be less confident regarding the products to be acquired [27,54,60,67,68]. This entails consumers avoiding their buying being focused on a specific brand and trying different alternatives, hence reducing their brand loyalty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since farmers rarely observe the antibiotic withdrawal periods, the milk could also have bacteria resistant to various antibiotics used to treat mastitis and other animal diseases. Apart from Nairobi county, raw milk is the most consumed milk type by both rural and urban consumers in Kenya [ 27 ]. One main reason for this preference is the low price of raw milk, which is 60–70% cheaper compared to pasteurized milk [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…With more than 265,000 hives, the average production per year is about 2,000 tons of honey (AVFA, 2016). Mtimet et al (2020) identified honey among the main organic products in Tunisia that need further attention to enhance its availability and access through the integration in mainstream sales channels which can reduce the gap between the purchase intention and actual purchase. However, Rached et al (2012) highlighted the availability of organic food products in Tunisian markets is very limited and the share of organic products in the Tunisian food budget remains low representing less than 1%.…”
Section: Introductionmentioning
confidence: 99%